1990
DOI: 10.1080/00071619000650021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity on hair formation and phosphatase activities of the blue-green alga (Cyanobacterium)Calothrix viguieriD253

Abstract: A strain of Calothrix viguieri, isolated originally from the surface of a mangrove root, showed marked morphological and physiological responses to the salinity of the medium. When grown to P limitation in a freshwater medium, each trichome ended in a long hair and the culture showed marked cell-bound phosphomonoesterase and phosphodiesterase activities. When grown with various P sources (inorganic and organic) to P limitation in medium including 5'6g 1-~ NaCI, hairs were absent, phosphomonoesterase activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…This mechanism seems to be efficient because son et al 1988), bacteria (Hassan & Pratt 1977, Chrdst parallel investigations have shown that phytoplankton & Overbeck 1990, Ammerman 1991), and algal culdoes not show any decrease in specific production (Jost tures (Kuenzler & Perras 1965, Cembella et al 1984, & Pollehne 1998. When phosphate concentrations are Mahasneh et al 1990, Hernandez et al 1993). Paasche at the detection limit in summer and hydrolysis rates & Erga (1988) and Chr6st (1991) found that these relaare about 10 to 30% h-', the organic phosphorous pool will be converted within 3 to 10 h. Under hydrochemical conditions in autumn, an organic phosphorous content of about 0.9 pM, and median hydrolysis rates of about 1 % h-', the phosphorous turnover needs about 100 h. A threshold of 1 pM phosphate could be defined for the regulatory function of phosphate on APA.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism seems to be efficient because son et al 1988), bacteria (Hassan & Pratt 1977, Chrdst parallel investigations have shown that phytoplankton & Overbeck 1990, Ammerman 1991), and algal culdoes not show any decrease in specific production (Jost tures (Kuenzler & Perras 1965, Cembella et al 1984, & Pollehne 1998. When phosphate concentrations are Mahasneh et al 1990, Hernandez et al 1993). Paasche at the detection limit in summer and hydrolysis rates & Erga (1988) and Chr6st (1991) found that these relaare about 10 to 30% h-', the organic phosphorous pool will be converted within 3 to 10 h. Under hydrochemical conditions in autumn, an organic phosphorous content of about 0.9 pM, and median hydrolysis rates of about 1 % h-', the phosphorous turnover needs about 100 h. A threshold of 1 pM phosphate could be defined for the regulatory function of phosphate on APA.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unclear whether the changes in APA with salinity are due to the influence of salinity itself or to the influence of particular ions. For example, Mahasneh et al (1990) ) on the regulation of phosphate uptake in Trichodesmium.…”
Section: Effect Of Salinity On Alkaline Phosphatase Activitymentioning
confidence: 99%
“…Dark conditions were also tested and were obtained by wrapping the bottle twice with aluminum foil. Practical details were given in [13,19]. Substrate was added to the bottles and bottles were tightly capped and run for 30 min.…”
Section: Phosphatase Assaymentioning
confidence: 99%